Single‐Cell Sequencing to Unveil the Mystery of Embryonic Development. Issue 2 (22nd December 2021) - Li, Zida; Lin, Feng; Zhong, Chu‐Han; Wang, Shue; Xue, Xufeng; Shao, Yue
Abstract: Embryonic development is a fundamental physiological process that can provide tremendous insights into stem cell biology and regenerative medicine. In this process, cell fate decision is highly heterogeneous and dynamic, and investigations at the single‐cell level can greatly facilitate the understanding of the molecular roadmap of embryonic development. Rapid advances in the technology of single‐cell sequencing offer a perfectly useful tool to fulfill this purpose. Despite its great promise, single‐cell sequencing is highly interdisciplinary, and successful applications in specific biological contexts require a general understanding of its diversity as well as the advantage versus limitations for each of its variants. Here, the technological principles of single‐cell sequencing are consolidated and its applications in the study of embryonic development are summarized. First, the technology basics are presented and the available tools for each step including cell isolation, library construction, sequencing, and data analysis are discussed. Then, the works that employed single‐cell sequencing are reviewed to investigate the specific processes of embryonic development, including preimplantation, peri‐implantation, gastrulation, and organogenesis. Further, insights are provided on existing challenges and future research directions. Abstract : Embryonic development provides tremendous insights into stem cell biology and regenerative medicine, and single‐cell sequencing can greatly facilitate these studies. In this review, the technological principles of single‐cell sequencing are consolidated, its applications in the study of embryonic development are summarized, and the future of this exciting research field is looked into.